A good quarrel : America's top legal reporters share stories from inside the Supreme Court - Goldman, Jerry; Johnson, Timothy Russell (University of Michigan Press, 2009)
Courtroom proceedings offer the thrill of a sporting event and the drama of a stage production as lawyers match wits, grill witnesses, and introduce eleventh-hour elements that may upend the course of a trial. The most decisive contests play out in the U.S. Supreme Court, where lawyers debate the meaning of the highest law-the Constitution-before the highest legal authorities-the nine justices. In A Good Quarrel, the nation's best court reporters discuss the most memorable cases of the past fifty years. These journalists not only recreate the key moments of the oral arguments, they analyze the attorneys' and justices' strategic use of rhetoric, logic, and emotional displays. In addition to a ringside account of each case, this volume provides web links to complete audio recordings of each oral argument and individual clips so that the reader can listen in on the debates that resolved a disputed presidential election, reconsidered women's rights, reassessed affirmative action, and decided many other pressing issues in the United States. Contributors: Charles Bierbauer Lyle Denniston Fred Graham Brent Kendall Steve Lash Richard Lazarus Dahlia Lithwick Tony Mauro Tim O'Brien David Savage Greg Stohr Nina Totenberg Timothy R. Johnson teaches in the political science department and the law school at the University of Minnesota. Jerry Goldman teaches political science at Northwestern University and directs the OYEZ Project, a multimedia archive devoted to the Supreme Court.